A Study on Formation of Candlestick Chart Patterns with Respect to the Indian Automobile Sector - Sangondimath, Anusha S.; Kamashetty, S. B. (Indian Journal of Research in Capital Markets, 2022)
The Indian economic scenario is changing and so are the spending and investment habits of Indian citizens. The investment choices of individual investors have switched from traditional physical assets such as gold, real estate, as well as bank deposits to stocks and other similar assets like bonds, debentures, and derivatives because of increased awareness of alternative investment options, improved technical analysis tools, ease of holding the investment, technological advancements in the form of user-friendly trading platforms, decreasing interest rates on traditional investment options, and the effect of a pandemic such as salary cuts, job losses, and an uncertain economic future, etc. According to a recent survey, the participation of retail investors in NIFTY alone grew to 45% in 2021 from 33% in 2016. The study intended to assist investors in the automobile sector by analyzing the success rate of some selected frequently occurring candlestick patterns and stating the patterns that have a high degree of reliability. The simple percentage analysis of the formations of the selected patterns over five years depicted that the bearish engulfing pattern and the bullish engulfing pattern were the most reliable patterns with a higher rate of success in comparison with the other selected patterns.